2020
DOI: 10.2147/idr.s273851
|View full text |Cite
|
Sign up to set email alerts
|

<p>Infection Prevention and Control Preparedness Level and Associated Determinants in 56 Acute Healthcare Facilities in Ghana</p>

Abstract: Background: Infection prevention and control (IPC) is a globally relevant aspect of all health systems impacting the health and safety of both patients and healthcare workers. However, best practices remain a challenge in healthcare delivery especially in resource limited situations. The primary objective of this study was to assess the infection prevention and control (IPC) preparedness levels of acute healthcare facilities in Ghana and to determine the factors associated with the overall IPC preparedness lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 18 publications
5
18
0
Order By: Relevance
“…Previous studies conducted in Ghana and Uganda have reported similar findings. The study from Ghana using five of the WHO IPCAF core components found that 41.1% of the health facilities had a ‘basic’ level of compliance similar to what we found [ 17 ]. However, unlike LUH, 37.5% of these facilities in Ghana had senior level leaders participating in IPC activities and a dedicated budget was allocated [ 17 ].…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Previous studies conducted in Ghana and Uganda have reported similar findings. The study from Ghana using five of the WHO IPCAF core components found that 41.1% of the health facilities had a ‘basic’ level of compliance similar to what we found [ 17 ]. However, unlike LUH, 37.5% of these facilities in Ghana had senior level leaders participating in IPC activities and a dedicated budget was allocated [ 17 ].…”
Section: Discussionsupporting
confidence: 78%
“…The study from Ghana using five of the WHO IPCAF core components found that 41.1% of the health facilities had a ‘basic’ level of compliance similar to what we found [ 17 ]. However, unlike LUH, 37.5% of these facilities in Ghana had senior level leaders participating in IPC activities and a dedicated budget was allocated [ 17 ]. In a study on implementation of IPC in health facilities in the Arua district of Uganda [ 18 ], 93.8% of these did not have an IPC committee, 93.8% reported an irregular supply of disposables and other supplies (such as gloves, soap, disinfectants), most facilities had no structures to monitor HCAI, and 72.6% never had in-service IPC training.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…From Jan 16 Weighted multivariable regression analysis showed that a lower total IPCAF score was significantly associated with low-income (-229•8 points lower [95% CI -352•3 to -107•3]) and lower-middle-income (-80•1 points lower [-148•1 to -12•1]) country status than high-income country status. A higher total IPCAF score was significantly associated with health-care facilities reporting their care level as Other (98•7 points higher [95% CI 36•7 to 160•6]) and categorised as a tertiary care facility (73 points higher [23•3 to 122•8]) rather than a primary care facility.…”
Section: Resultsmentioning
confidence: 99%
“…A study that assessed IPC initiatives in Ghana assessed five out of eight possible IPC components of the standard tool in the facilities. 19 Thus, a more comprehensive assessment is needed to ensure all gaps in practice are identified and addressed for health and safety. This will provide guidance on the need for pragmatic interventions through AMS and IPC to address and/or contain the high burden of AMR.…”
Section: Introductionmentioning
confidence: 99%